2022
DOI: 10.1038/s41396-021-01119-1
|View full text |Cite
|
Sign up to set email alerts
|

Human gut-microbiome-derived propionate coordinates proteasomal degradation via HECTD2 upregulation to target EHMT2 in colorectal cancer

Abstract: The human microbiome plays an essential role in the human immune system, food digestion, and protection from harmful bacteria by colonizing the human intestine. Recently, although the human microbiome affects colorectal cancer (CRC) treatment, the mode of action between the microbiome and CRC remains unclear. This study showed that propionate suppressed CRC growth by promoting the proteasomal degradation of euchromatic histone-lysine N-methyltransferase 2 (EHMT2) through HECT domain E3 ubiquitin protein ligase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 47 publications
1
44
0
Order By: Relevance
“…Major SCFAs include acetate, butyrate, and propionate. Butyrate could inhibit the motility of colorectal cancer cells by deactivating Akt/ERK signaling ( Li et al, 2017 ); acetate was shown to promote the expression of anti-inflammatory cytokines and reduce the generation of pro-inflammatory factors and NF-κB pathway activation in CRC cells ( Tedelind et al, 2007 ); and propionate suppressed CRC growth by promoting the proteasomal degradation of euchromatic histone-lysine N-methyltransferase 2 (EHMT2) through HECT domain E3 ubiquitin protein ligase 2 (HECTD2) upregulation ( Ryu et al, 2022 ). Secondary bile acids, lactate, trimethylamine N-oxide (TMAO), N-nitroso compounds, acetaldehyde, 4-hydroxyphenylacetic acid, phenylacetic acid, and phenol are related to CRC ( Mohseni et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Major SCFAs include acetate, butyrate, and propionate. Butyrate could inhibit the motility of colorectal cancer cells by deactivating Akt/ERK signaling ( Li et al, 2017 ); acetate was shown to promote the expression of anti-inflammatory cytokines and reduce the generation of pro-inflammatory factors and NF-κB pathway activation in CRC cells ( Tedelind et al, 2007 ); and propionate suppressed CRC growth by promoting the proteasomal degradation of euchromatic histone-lysine N-methyltransferase 2 (EHMT2) through HECT domain E3 ubiquitin protein ligase 2 (HECTD2) upregulation ( Ryu et al, 2022 ). Secondary bile acids, lactate, trimethylamine N-oxide (TMAO), N-nitroso compounds, acetaldehyde, 4-hydroxyphenylacetic acid, phenylacetic acid, and phenol are related to CRC ( Mohseni et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of commensal bacterial species have been reported to be associated with the enhanced efficacy of ICIs, including B. thetaiotaomicron (23), B. fragilis (24), B. cellulosilyticus (25), Parabacteroides distasonis (26), B. salyersiae (27), and B. uniformis (13). In this study, our metagenomic analysis showed that FMT significantly upregulated the abundance of those potentially beneficial species, particularly those species from Bacteroides genus (Figures 2C, E).…”
Section: Discussionmentioning
confidence: 99%
“…the expression of IL-10) and mediate intestinal homeostasis (29). B. thetaiotaomicron is also able to inhibit the growth of CRC cells via its metabolite propionate (23). Another Bacteroides species B. fragilis is associated with the favorable clinical outcome of CTLA-4 inhibitors (24) via inducing regulatory T cells to secrete IL-10 through the immunomodulatory molecule polysaccharide A (PSA) of B. fragilis (30).…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of commensal bacterial species have been reported to enhance the efficacy of ICIs, including B. thetaiotaomicron (23), B. fragilis (24), B. cellulosilyticus (25), Parabacteroides distasonis (26), B. salyersiae (27), and B. uniformis (13). In this study, our metagenomic analysis showed that FMT significantly upregulated the abundance of those aforementioned species, particularly those species from Bacteroides genus ( Fig.…”
Section: Discussionmentioning
confidence: 99%